The Effect of Learning Model and Critical Thinking Skills on Students’ Learning Outcomes in Pancasila Education Learning - Samiruddin; Muhammad Idrus (Jurnal Ilmiah Sekolah Dasar, 2025)
Most students consider Pancasila education to be a complex and difficult subject, resulting in low scores. Challenges that arise can be overcome through the use of innovative learning models. The aim of this study is to analyze the impact of learning models and critical thinking skills on student learning outcomes in Pancasila education learning. This type of research is an experiment with a 2 x 2 treatment by level design. Using a multistage random sampling technique, 60 students were randomly chosen to make up the research sample. Instruments were used to gather data for this investigation. Analysis of variance (ANOVA) was used for the statistical analysis, and the significance threshold was set at 0.05. The findings of the study showed that the learning outcomes of students taught with the discovery learning model were higher than those of students taught with the project-based learning model in the group of students with high critical thinking skills. Conversely, students with low critical thinking skills who were taught with the discovery learning model and the project-based learning model did not show significant differences in learning outcomes in Pancasila education learning. These findings indicate that the discovery learning and project-based learning models have a significant influence on improving student learning outcomes in Pancasila education learning, both for students with high critical thinking skills and students with low critical thinking skills.